Metodologia para avaliação do desempenho de tintas para decoração digital de revestimentos cerâmicos - Lot, Ana Virgínia (Universidade Federal de São Carlos, 2016)
Brazil plays an important role in the consumption and production of ceramic tiles nowadays. The decoration of tiles by digital inkjet printing, due to its technical and aesthetic advantages, is a spreading technology and has already been adopted in the national industry. Ink sets acquired from different manufacturers differ in their extension behavior on the ceramic surface, in the definition of the printed pattern, in the range of printable colors, and in the ink yield, square meters of a same decoration that can be printed for unit volume of ink. Due to the peculiarities of this technology, there is still no methodology for evaluating the performance of the inks and there is very little published on this topic. This paper proposes a methodology for a comparative evaluation of the performance of industrial inks, aiming to help in the selection of these inputs by ceramic tiles producers. Drops of the evaluated inks were applied on a defined ceramic substrate. The colorimetric behavior and the extension of the ink were assessed as indicative parameters of the image quality and yield of the inks. The colorimetric characteristics and the size of the points produced with inks from different suppliers were significantly different for all the four colors of the inks evaluated. For all these colors, the results point to similar conclusions, demonstrating the validity of the method. Some technical characteristics of the inks were studied to identify the reasons for the different behaviors observed. The color differences between inks of different suppliers are explained by the different pigment phases in each composition of ink. The extension of the inks were greatly influenced by its viscosities. The more viscous inks, due to greater difficulty in penetrating the ceramic substrate, expanded more over it.
Keywords: Decoração digital; Decoração por jato de tinta; Revestimentos cerâmicos; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA